TRADISI BERBALAS PANTUN ADAT PERNIKAHAN MASYARAKAT BENGKULU - Rhanda Syeptian Mardika; Sarwit Sarwono; Amril Canrhas (Jurnal Korpus, 2018)
This research entitled "Tradition of poem Reciprocated by Wedding ritual of Bengkulu Community". The poem reciprocated tradition is an ancient tradition which realized in communication, performances, containing cultural values, religion, ethics, and aesthetics and contains of text elements of text elements, place, instrument, audience and show context. To guide and direct this research writer used  folklore theory, oral tradition, and performaing arts. The data were collected by observation techniques, interviews, and documentation. The discussion result shows that the oral tradition of poem reciprocated has a noble value, namely socialization, aesthetics, religion, culture and history, on hereditary in Bengkulu society, especially in Penurunan and Sawah Lebar district. The traditions of poem reciprocated has been alive and developing in this region. the five stages of Poem reciprocated in the process of marriage ritual in Bengkulu community as follow are : 1) Telling/ delivering the intentions,  the intentions is delivered by elderly family from the groom. 2) Propose, the traditional head of the groom delivers the groom from man’s family. 3) handover the gifts, the delivery of dowries delivers from man’s family to the woman’s family to the woman’s family. 4) the marriage agreement. 5) The bride and groom is coming up, bring the groom to the groom to the bride’s house side by side on the aisle. The conten of the five stages of poem reciprocated traditions in the marriage ritual of Bengkulu people is guided by the community of supporters in their daily life, they belive that the social value in poem reciprocated, as a norm in the life demands and must be upheldKeywords: tradition, poem reciprocated